2014
DOI: 10.1021/cs500326e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Computational Studies of N-Heterocyclic Carbene or Phosphine-Containing Copper(I) Complexes for the Synthesis of 5-Iodo-1,2,3-Triazoles

Abstract: Two complementary catalytic systems are reported for the 1,3-dipolar cycloaddition of azides and iodoalkynes. These are based on two commercially available/readily available copper complexes, [CuCl­(IPr)] or [CuI­(PPh3)3], which are active at low metal loadings (PPh3 system) or in the absence of any other additive (IPr system). These systems were used for the first reported mechanistic studies on this particular reaction. An experimental/computational-DFT approach allowed to establish that (1) some iodoalkynes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 85 publications
4
55
1
Order By: Relevance
“…Among the examples in Scheme , the formation of 5‐iodo‐1,2,3‐triazole has been studied most thoroughly on both synthetic method and mechanistic fronts 10,32,61. A variety of methods for its synthesis are available, many of which start from a terminal alkyne instead of an iodoalkyne, and an electrophilic iodination agent (ICl or N ‐bromosuccinimide (NBS)/CuI) 62.…”
Section: Cuaac Reactions Involving Internal Alkynesmentioning
confidence: 99%
“…Among the examples in Scheme , the formation of 5‐iodo‐1,2,3‐triazole has been studied most thoroughly on both synthetic method and mechanistic fronts 10,32,61. A variety of methods for its synthesis are available, many of which start from a terminal alkyne instead of an iodoalkyne, and an electrophilic iodination agent (ICl or N ‐bromosuccinimide (NBS)/CuI) 62.…”
Section: Cuaac Reactions Involving Internal Alkynesmentioning
confidence: 99%
“…Several reports in the literature feature the importance of nitrogen additives in this reaction, including our own work with the related [CuI(PPh 3 ) 3 ] complex …”
Section: Resultsmentioning
confidence: 99%
“…Fokin first suggested that cleavage of the carbon–iodine bond is not required for the cycloaddition to take place . Our DFT studies supported this and showed that either formation of a copper(III) metallacycle or direct activation of the iodoalkyne by π‐coordination of the copper catalyst accounted for the copper‐acceleration effect and regioselectivity of this cycloaddition reaction …”
Section: Introductionmentioning
confidence: 99%
“…Among the 5‐halo‐1,2,3‐triazoles, the synthesis of 5‐chloro‐1,2,3‐triazoles ( 44 ) was the most difficult task and there are few chemoselective procedures for this purpose in literature. As shown in Scheme , this mild and convenient tandem reaction method is a valuable addition.…”
Section: Premade 1‐copper(i) Alkynes In Cycloadditionsmentioning
confidence: 99%
“…In our earlier works (see Scheme ), 1‐iodoalkyne was produced quantitatively within 10 minutes by the reaction of the premade 1‐copper(I) alkyne and NIS . Since the synthesis and storage of 1‐iodoalkyne are not convenient using the existing methods in literature, we tried to use the combination of the premade 1‐copper(I) alkyne/molecule iodine as a synthetic equivalent of 1‐iodoalkyne. As shown in Scheme , when the mixture of the premade 1‐copper(I) alkyne 1 and azide 5 was treated by molecule iodine, the corresponding 5‐iodo‐1,4,5‐trisubstiuted 1,2,3‐triazoles 54 were obtained in high yields within 15 minutes.…”
Section: Premade 1‐copper(i) Alkynes In Cycloadditionsmentioning
confidence: 99%